PENGEMBANGAN DESAIN PEMBELAJARAN PAI UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) PESERTA DIDIK - Qurrota Akyunin; Nur Fiza; Salman Ahyani (Jurnal Pema Tarbiyah, 2026)
Islamic Religious Education (PAI) learning in schools still predominantly focuses on lower-order thinking skills, which has limited the development of students’ higher order thinking skills (HOTS). This situation highlights the need for an instructional design that can encourage students’ critical, analytical, and evaluative thinking abilities. Therefore, this study aims to develop a HOTS-oriented PAI instructional design and to determine its feasibility and effectiveness in improving students’ higher order thinking skills. This study employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research participants consisted of PAI teachers and secondary school students. Data were collected through interviews, expert validation questionnaires, HOTS tests, and classroom observations. The data were analyzed using descriptive qualitative and quantitative techniques. The findings indicate that the developed HOTS-oriented PAI instructional design is feasible based on expert validation results and effective in enhancing students’ higher order thinking skills. Thus, this instructional design can serve as an innovative and meaningful alternative for improving Islamic Religious Education learning.